2017
DOI: 10.1111/nmo.13077
|View full text |Cite
|
Sign up to set email alerts
|

The effects and mechanism of action of methane on ileal motor function

Abstract: The actions of methane on the intestine are influenced by the cholinergic pathway of the enteric nervous system. Our findings support the classification of methane as a gasotransmitter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…showed that direct infusion of CH 4 in animals slows intestinal transit, and also showed that segments of guinea pig ileum exhibit increased contractile impulses when bathed in CH 4 ( 33 ). CH 4 appears to cause dysregulation in motility by amplifying neuronal activity in the intestine through the anticholinergic pathway ( 34 ). In humans, a study showed that the degree of constipation correlated with breath CH 4 levels in subjects with IBS ( 31 ).…”
Section: Prevalence Of Sibo In Ibsmentioning
confidence: 99%
“…showed that direct infusion of CH 4 in animals slows intestinal transit, and also showed that segments of guinea pig ileum exhibit increased contractile impulses when bathed in CH 4 ( 33 ). CH 4 appears to cause dysregulation in motility by amplifying neuronal activity in the intestine through the anticholinergic pathway ( 34 ). In humans, a study showed that the degree of constipation correlated with breath CH 4 levels in subjects with IBS ( 31 ).…”
Section: Prevalence Of Sibo In Ibsmentioning
confidence: 99%
“…Methane, therefore, significantly increased calcium fluorescence while this increase was attenuated following atropine infusion. EFS and the fluorescence, however, remain unchanged with calcium infusions, tetrodotoxin (TTX), and guanethidine [6,20,25].…”
Section: Reviewmentioning
confidence: 99%
“…These microbiotas generate methane gas from the fermentation of endogenous and exogenous carbohydrates. Methane, which was long considered to be an inert gas, is now known to behave as a neurotransmitter that has paved the path for pharmacologic therapy to create novel drugs targetting methanogenesis, in particular, to control C-IBS [6-7]. This unique correlation of irritable bowel syndrome with methane makes it a center of attraction and further stresses on how important it is to study this association.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in both animal models and humans studies, CH 4 has been associated with a slowed intestinal transit time [6, 7], and suppression of CH 4 production with antibiotics has been associated with improvement in constipation [8]. Although the mechanism is not fully elucidated, CH 4 is thought to affect intestinal smooth muscle contraction as a gasotransmitter via a cholinergic pathway [9]. Supporting its role in the parasympathetic pathway, Robinson-Papp et al [10] have shown that patients with vagal dysfunction have increased breath CH 4 .…”
Section: Introductionmentioning
confidence: 99%